India's market society : three essays in political economy - Harriss-White, Barbara (Readings (Three Essays Press)., 2005)
What kind of market society is India becoming? In these three essays author looks at the non market and non state institutions which shape India s market society. The first essay focuses on markets for land, labour and the essential commodities of staple food and contextualises the non market, non state institutions in the ground realities of the regulative behaviour of the Indian state. The second essay examines caste and shows how caste is being reworked in the contemporary era to be an instrument of corporatist regulation. The third essay looks into the implications of India s religious pluralism for her economy, and discusses an important issue: where India s minorities are sited in the economy? The author examine the ground realities of the markets which form the building blocks of Indian capitalism - together with the deprivations of people who are casualties of the workings of these markets and this capitalism. 1. Market Romanticism and India s Regulative Order 2. Caste Corporatist Capitalism: Civil Society and Accumulation (with Elisabetta Basile) 3. India s Religions and the Economy